Transposição de serapilheira em processo de restauração ambiental: análise de fungos endomicorrízicos no município de Cabreúva, SP. - Giacomini, Luciana Aparecida (2019)
Many natural areas of high biological diversity and endemism, such as those in the Atlantic Forest domain in the southeastern state of São Paulo, have been degraded to meet man's need to convert these areas into agricultural plantations, livestock breeding and other uses. ground. The ecological restoration technique, through the transposition of the forest blanket to degraded or disturbed areas, allows the reestablishment of the ecological processes and can contribute with the increase of the community of microorganisms. Fungi present in the soil microbiota are considered key elements in the nutrient cycling of organic matter deposited in the soil. The arbuscular mycorrhizal fungi belonging to the phylum Glomeromycota associate the plants and are considered obligatory biotrophic; in establishing the symbiosis contribute to the availability of nutrients from the soil to the plants. The objective of this work was to evaluate the influence of the transposition nucleation technique of the second organic litter sub-horizon in the community of mycorrhizal fungi in a disturbed area located in the municipality of Cabreúva, SP. Ten plots were delimited in the experimental unit, being five control plots and five plots with treatment. Two samplings were carried out, the first in October 2017 and the second in July 2018. In these samplings, individual and integrated samples of the soil plots were collected to analyze the physical and chemical characteristics of the soil, the community of mycorrhizal fungi and the number of glomerospores. A total of 27 species were distributed in eight genera: Pacispora (1 species), Diversispora (1), Funneliformis (1), Archaeospora (2), Scutellospora (3), Dentiscutata (4), Acaulospora (5) and Glomus, belonging to six families. It was concluded that the edaphic conditions of the experimental unit are consistent with the presence of arbuscular mycorrhizal fungi. The transposed organic matter did not promote an increase in species richness and didn’t facilitate the colonization of plant species in the area, whereas gravimetric and grassy moisture may have influenced the richness. The multivariate permutation analysis detected differences in the composition of the species between the seasons and the density of glomerospores decreased in the dry season.